Kos dan faedah pembangunan sistem maklumat geografi untuk sistem pentadbiran kadaran Majlis Perbandaran Sandakan - Ronggitom, Johny (2008)
Cost Benefits Analysis (CBA) is an appraisal investment method that serves as a Valuation Development Program Guideline for government in Malaysia including Local Government under Surat Pekeliling Am Bil. 3 Tahun 2005. In this research CBA is used to appraise the capital investment on system development in Sandakan Municipal Council's assessment administration. The costs and benefits of Geographic Information System (GIS) development attained is compared with the cost and benefits from other alternatives which is the current status quo and the current improvable alternative system. The purpose of comparing the costs and benefits are to determine the financial liability and economy in every alternative, which serve as the foundation in making a quality decision in selecting the most suitable, competent, efficient and capable in the process of development. All ten methodologies had been carried out with the four most important methods: (a) GIS model; (b) costs estimation; (c) benefits estimation; and (d) CBA itself. The final result of this research that the net present value of GIS development alternatives shows the highest with the amount of RM44.3 million and payback period is 2 years and 0.5 month. Ratio benefits to costs and ratio increase benefits to costs for GIS development alternatives also the highest with 13.22 and 3.47 respectively. Meanwhile, the comparison relative value for both quantitative and qualitative benefits for GIS development also showed the highest, 3.36. The summary of this research shows that GIS development is the best and suitable application for administration assessment system in Sandakan Municipal Council based on the discounted gross value and the cost and benefits ratio shows the highest for quantitative and qualitative benefits.